1999
DOI: 10.1097/00006123-199911000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Hydrocephalus after Aneurysmal Subarachnoid Hemorrhage

Abstract: Hydrocephalus seems to have a multifactorial etiology. Knowledge of risk factors related to the occurrence of hydrocephalus may help guide neurosurgeons in the long-term care of patients who have experienced aneurysmal SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
5
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 39 publications
8
94
5
2
Order By: Relevance
“…In their study consisting of 897 cases, Sheehan et al detected that GOS was the factor that showed a significant correlation (29). In our study, 76.2% of the patients were GOS grade 1 and grade 2, and this result was statistically significant (p<0.05) (Table VIII) ( Figure 6).…”
Section: █ Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…In their study consisting of 897 cases, Sheehan et al detected that GOS was the factor that showed a significant correlation (29). In our study, 76.2% of the patients were GOS grade 1 and grade 2, and this result was statistically significant (p<0.05) (Table VIII) ( Figure 6).…”
Section: █ Resultssupporting
confidence: 66%
“…It was shown that acute hydrocephalus and intraventricular hemorrhage, severe clinical course, hypertension, alcoholism, gender, large aneurysm size and infections such as pneumonia and meningitis were important factors in the development of chronic hydrocephalus (12,13,22,29). In our study, an increase was observed in the incidence of hydrocephalus in patients with meningitis and it was statistically significant (p<0.05) (Table IX) ( Figure 7).…”
Section: █ Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Se asocia a un peor pronóstico y tiene una relación estrecha con la cantidad de sangre intraventricular y los sangramientos recurrentes 27 .…”
Section: Hidrocefaliaunclassified
“…En la fase aguda de la HSA, la dilatación del sistema ventricular como consecuencia de la formación de coágulos en las cisternas basales y el taponamiento de las vellosidades aracnoideas, por fi brina proveniente de la sangre extravasada provoca aumento de la presión intracraneal (PIC) 27 . En este contexto, los resultados del estudio con DTC ofrece información indirecta sobre el estado de PIC a través de los cambios que se registren en el índice de pulsatilidad (IP) de las arterias cerebrales media 28 .…”
Section: Hidrocefaliaunclassified